Pedagogical Utilisation of ICTs in Teaching Practice of Undergraduate Students - Μπεαζίδου Ελευθερία; Ρουσσάκης Ιωάννης; Μπότσογλου Καφένια; Καραγιαννίδης Χαράλαμπος (Education Sciences, 2020)
This research was conducted in 57 future teachers of the Pedagogical Department of Special Needs Education who carried out their practical training in Primary Schools of Magnesia, aiming to contribute in the above direction. The survey data was collected a) from the qualitative analysis of the "teaching plans" that student had the obligation to organize and implement in the classroom b) from the quantitative analysis of student’s answers to the questionnaire which designed for this research. The results showed applications of technology in educational process as well as the web quest for course preparation and the creation texts (additional exercises in the subject) were the mainly of them. Few students had supported their teaching by web 2.0 tools or other educational software applications.